Working fathers: determinants of time allocation to work and family roles. (2nd July 2016) - Fong, Man Mandy; Bainbridge, Hugh T. J.
ABSTRACT: Time is a valuable but scarce resource in both work and family domains. The 'zero-sum' nature of time means that an increase in hours allocated to work decreases that which is available for family responsibilities and vice versa. The work-family literature indicates that there are gender differences in work-family decision-making; however, the time use decisions of working fathers has received limited attention. This research considers behavioural changes in time allocation to work and non-work activities of male employees after their transition to fatherhood. The determinants of time allocated to work and family roles for fathers are considered via an analysis of data from the Household, Income and Labour Dynamics in Australia survey. Results indicated that fathers' country of birth and satisfaction with their partner were associated with most of their time use decisions.